The genome sequence of the malaria mosquito, Anopheles funestus, Giles, 1900 [version 1; peer review: 2 approved] - James Torrance; Ying Sims; Marcela Uliano-Silva; Sarah Pelan; Ousman Akone-Ella; Diego Ayala; Harriet Johnson; Pierre Kengne; Ksenia Krasheninnikova; Haynes Heaton; Joanna Collins; Alan Tracey; et al. (Wellcome Open Research, 2022)
We present a genome assembly from an individual female Anopheles funestus (the malaria mosquito; Arthropoda; Insecta; Diptera; Culicidae). The genome sequence is 251 megabases in span. The majority of the assembly is scaffolded into three chromosomal pseudomolecules with the X sex chromosome assembled. The complete mitochondrial genome was also assembled and is 15.4 kilobases in length.